Emerging challenges in assessing bio-based nanosystems’ behaviour under in vitro digestion focused on food applications – a critical view and future perspectives - Madalena, Daniel (2022)
The current consumers’ demand for high quality food products together with the growing awareness regarding the link between health and nutrition has led to the development of novel food products with added functionality. Such functionality can be modulated by adding bio-based nanosystems that can improve the bioaccessibility of bioactive compounds and facilitate nutrient absorption. However, these functional properties can be significantly affected by the adverse conditions (e.g., low pH, presence of enzymes, salts) of the gastrointestinal tract. As such, understanding the behaviour of such delivery systems under digestion conditions is of utmost importance and several analytical tools and in vitro digestion models have been used for this purpose. This review summarizes the latest updates on nanosystems’ performance under in vitro digestion and provides critical insights related to important and complementary analytical tools (e.g., rheology, Raman spectroscopy, x-ray scattering) used to assess their performance throughout digestion. Furthermore, the most prominent and frequent challenges associated with such in vitro analyses are also described, together with the current trends regarding the development of in vitro digestion models and some considerations that should be undertaken for their validation. Efforts must be made towards developing reliable and standard in vitro digestion models that use sophisticated analytical techniques to further expand the knowledge regarding nanosystems’ behaviour under in vitro digestion conditions.